Radiographic Follow-Up during Orthodontic Treatment for Early Diagnosis of Sequential Supernumerary Teeth - Selma Sano Suga; Paula de Castro Kruly; Talissa Mayer Garrido; Marise Sano Suga Matumoto; Uhana Seifert Guimarães Suga; Raquel Sano Suga Terada (Case Reports in Dentistry)
Most supernumerary teeth are impacted and asymptomatic. Objective. The aim of this paper is to describe two cases of sequential development of supernumerary teeth in the mandibular premolar region, identified during orthodontic treatment. Reports. The first case describes the radiographic follow-up of a female patient that presented a supernumerary tooth at the age of 9 years and 10 months in the right mandibular premolar region, followed by a further supernumerary tooth in the left mandibular premolar region identified at the age of 11 years and 3 months. In the second case, the radiographic follow-up of a male patient demonstrated 3 supernumerary teeth in the premolar region at the age of 16 years. During orthognathic surgery planning at the age of 20 years and 5 months, a supplemental supernumerary tooth was found in the left mandibular region. Conclusion. Considering the late developing of supernumerary premolars, appropriate follow-up with panoramic radiographs of patients with previous experience of supernumerary teeth is essential for early diagnosis of supplemental premolars to prevent possible complications.